2009
DOI: 10.1002/jnr.22172
|View full text |Cite
|
Sign up to set email alerts
|

Memantine lowers amyloid‐β peptide levels in neuronal cultures and in APP/PS1 transgenic mice

Abstract: Memantine is a moderate-affinity, uncompetitive N-methyl-D-aspartate (NMDA) receptor antagonist that stabilizes cognitive, functional, and behavioral decline in patients with moderate to severe Alzheimer's disease (AD). In AD, the extracellular deposition of fibrillogenic amyloid-beta peptides (Aβ) occurs due to aberrant processing of the full-length Aβ precursor protein (APP). Memantine protects neurons from the neurotoxic effects of Aβ and improves cognition in transgenic mice with high brain levels of Aβ. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 67 publications
4
86
2
Order By: Relevance
“…These differences would result in disparities between their absolute CNS drug levels and exposure time course. Indeed, ketamine has previously been shown to display a very short half-life (∼13 min) in mice (Maxwell et al 2006) whereas memantine displays a half-life of around 2-4 h (Alley et al 2010). To overcome the differences in biological half-life, we could have considered to shorten the [ 14 C]2-DG uptake period to 5-15 min as in previous studies (Duncan et al 1998b;Miyamoto et al 2000).…”
Section: Discussionmentioning
confidence: 96%
“…These differences would result in disparities between their absolute CNS drug levels and exposure time course. Indeed, ketamine has previously been shown to display a very short half-life (∼13 min) in mice (Maxwell et al 2006) whereas memantine displays a half-life of around 2-4 h (Alley et al 2010). To overcome the differences in biological half-life, we could have considered to shorten the [ 14 C]2-DG uptake period to 5-15 min as in previous studies (Duncan et al 1998b;Miyamoto et al 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, the only drug thus far shown to slow the progression of AD in some patients is memantine, an NMDA receptor blocker [54]. Moreover, recent studies have shown that memantine, which is a channel-blocking drug with a fast off rate and voltage-dependent binding properties [54], lowers Aβ levels in neuronal cultures and in APP/PS1 double transgenic mice [55], and reduces AD-like neuropathology in 3xTgAD mice [56]. Memantine's ability to protect neuronal cells against degeneration, to increase cell viability and/or metabolic activity, and to lower amyloidogenic pathway is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…A phospho-to-pan-ERK ratio was determined for each sample and plotted. Please see Alley et al, 2010 for a review of the immunoblotting methodology (Alley et al, 2010). …”
Section: Methodsmentioning
confidence: 99%